The Art of Soul Care ~ Converging Art and Spirituality as a Pastoral Theology of Discernment for Acedia A Phenomenological Case Study - LaRiviere, Vivianne (Université Saint-Paul / Saint Paul University, 2019)
Under the umbrella of theology and the arts, this art-based research focused on the possibilities of how the elements of converging art and spirituality may guide us toward pathways of spiritual renewal and transformation. Though the practice is designed to question many of the challenges we presently face in our contemporary Western world society, this phenomenological case study took on a particular task of discernment for the potentially soul-killing spiritual illness presently known as acedia. Acedia is rooted in the historical elements of Christian monasticism. Though systemized as ‘despondency’ by a 4th century, Christian monk known as Evagrius of Ponticus, the spiritual illness of the soul has been described as many other things. ‘The noon-day demon,’ 8th deadly sin, precursor to sloth, and despair are some of its familiar descriptions. Acedia has a long list of symptoms: laziness, apathy, and depression to name a few; restlessness and anxiety mentioned frequently. The 17th century Greek etymology of the word means ‘absence of care.’ Given the present day disregard toward ecological and environmental concerns, the ongoing historical exodus of refugees and migrants around the world, the cascading cries of war, capitalist impunities, rogue political disdain, and the lack of concern for the inherent worth of so many on our planet, to regard acedia as a global social stigma is sadly a viable consideration of our times. Acedia’s ultimate danger of suicide may conversely find its way into the very fabric of humanity’s existence, as we notably wrestle with a culture that is leaning more and more toward anxiety, restlessness and less and less away from a principled morality of care. Although acedia’s trajectory of possible causes and dangers is evident even in the 5 most rudimentary introductions on the topic, the literature lacks detailed accounts of contemporary pastoral education. Investigating acedia as a causality of identity crisis, I questioned if the convergence of art and spirituality – as a practical theology and the arts – could not only serve as a pastoral practice of discernment for acedia, but also offer the possibility of transformation; asking the existential question: Who am I? Addressing this question with five sub-text questions: What do I believe? What do I value? What is my purpose? What are my challenges? Who am I called to become? A phenomenological case study – seeking to determine what is meaningful – was the most appropriate methodological approach for this project highlighting the experience of six participants who took part in a four day (once-a-week) – five-module retreat. The participants, with varied religious beliefs, ranging in age from 34 – 69, demonstrating an initial interest after public announcement of the project, were selected via a preliminary interview process. The method was designed with material presentation, discussion, meditation, and art time. And the sharing and witnessing of such, culminating with the writing of a renewed spiritual covenant – a mission statement outlining what each participant believes, values, and ‘who we are called to become’ as it aligns with one’s purpose. The results of the research suggest a practical theology of the arts merits consideration as a feasible practice of discernment for acedia. The participants collectively shared of the positive experience of the project, and overall described some shape of transformative experience. Thematically, connection is investigated as a prime and imperative facet of ‘meaning.’ As we have serious deliberation of the widening field of method and methodology, the parameters of theology and the arts might help define future qualitative 6 research. Furthermore, a practical theology and the arts may provide considerable weight to the field of practical theology as a sustainable extension of how Divinity inspires through imagery, as the first language of the soul. The convergence of art and spirituality – as an art-based research – may provide us with connections otherwise left unconsidered, as it may offer responses that are far more intricate, intimate and vulnerable, as its nature tends to reveal agendas in a transparent manner. The world of abstract and symbolism speak to places of significance that otherwise may go undetected. Structured as qualitative research, the study offers considerations for the practices of pastoral care, and offers ideas for curriculum development. There is also supporting qualitative evidence to support the study of ethics. Included in the final recommendations are to correlate theology, and theology and the arts with both the fields of philosophy and psychology as a means of investigating acedia as a psychological complex, and its potential association with trauma, to contribute to the advancement of these fields, as well as to consider its potential in the field of ethics, and care. Additionally, to consider that acedia with an underlying facet of fear, if not directly defined as, is nonetheless associated with the fear of suffering. Pastoral, theological and practical considerations are also listed.
Keywords: Pastoral theology; practical theology; theology and the arts; practical theology and the arts; acedia; practical theology and spirituality; spirituality; leadership; discernment; ethics; care; art-based research; retreat formation; education; curriculum; practitioners; spiritual practitioners; spiritual care practitioners